Utilisation of Wordwall Application as a Media for Evaluating Maharah Al Kitabah: Pemanfaatan Aplikasi Wordwall sebagai Media Evaluasi Maharah Al Kitabah - Khairanis, Retisfa; Hasaniyah, Nur; Al Anshory, Abdul Muntaqim (ELOQUENCE : Journal of Foreign Language, 2025)
Background: This research is motivated by the importance of innovation in learning evaluation media, especially in improving the quality of the Maharah Al Kitabah evaluation at Mutiara Al Madani Islamic Junior High School. So far, the evaluation methods used are still conventional and less able to arouse students' interest in learning. Based on observations and interviews with Arabic language teachers, it is known that the Wordwall application has been utilized as an alternative evaluation media that is more interesting and interactive. Purpose: This research aims to describe the utilization of Wordwall application as an evaluation media for Maharah Al Kitabah. Method: This research used a qualitative approach with a descriptive design. Data sources consisted of Arabic teachers and learning activities in class VIII. The sample was selected through purposive sampling, while the data were collected through participatory observation and semi-structured interviews. The instruments used were observation guidelines and interview guidelines. The data analysis procedure followed the stages of data reduction, data presentation, and conclusion drawing. Results and Discussion: The results showed that the use of Wordwall helped teachers in preparing varied and fun evaluations and was able to increased student involvement in the learning process of Maharah Al Kitabah. This research also fills the gap related to the lack of utilisation of digital media in Arabic learning evaluation. Conclusions and Implications: In conclusion, Wordwall is effectively used as an evaluation medium for Maharah Al Kitabah and has a positive impact on students' learning process. The implication is that teachers need to continue to develop the utilisation of digital media in learning evaluation and become a reference for further research in the field of Arabic language education.